2009
DOI: 10.1038/leu.2009.247
|View full text |Cite
|
Sign up to set email alerts
|

Pirin downregulation is a feature of AML and leads to impairment of terminal myeloid differentiation

Abstract: Terminal differentiation of blood cells requires the concerted action of a series of transcription factors that are expressed at specific stages of maturation and function in a cell-type and dosage-dependent manner. Leukemogenic oncoproteins block differentiation by subverting the normal transcriptional status of hematopoietic precursor cells. Pirin (PIR) is a putative transcriptional regulator whose expression is silenced in cells bearing the acute myeloid leukemia-1 eight-twenty-one (AML1/ETO) and promyelocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…It encodes for the iron-binding nuclear protein pirin, a transcriptional regulator, and has been described as an oncogene [49] and promoter of metastatic tumor growth [50] on one hand and as a tumor suppressor gene on the other [51] in many solid cancers, but never before in glioma. In acute myeloid leukemia (AML), PIR was linked to terminal differentiation of myeloid precursors with a downregulation of PIR possibly related to the differentiation arrest observed in AML [52]. By contrast, overexpression of PIR was involved in inhibition of cellular senescence in melanocytic cells, resulting in transformation to melanoma [53].…”
Section: Discussionmentioning
confidence: 99%
“…It encodes for the iron-binding nuclear protein pirin, a transcriptional regulator, and has been described as an oncogene [49] and promoter of metastatic tumor growth [50] on one hand and as a tumor suppressor gene on the other [51] in many solid cancers, but never before in glioma. In acute myeloid leukemia (AML), PIR was linked to terminal differentiation of myeloid precursors with a downregulation of PIR possibly related to the differentiation arrest observed in AML [52]. By contrast, overexpression of PIR was involved in inhibition of cellular senescence in melanocytic cells, resulting in transformation to melanoma [53].…”
Section: Discussionmentioning
confidence: 99%
“…We recently observed that PIR knockdown in hematopoietic precursors impairs terminal myeloid differentiation, and its down-regulation in leukemias may therefore contribute to the maturation arrest characteristic of acute myeloid leukemia. 31 The molecular mechanisms underlying the role of PIR in counteracting senescence remain unknown. PIR may contribute to this phenotype by modulating the transcription of key regulators of senescence, but it may also exert its function through other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In progenitor cells, the activation of pirin is an important event that alters the transcription profile of the cell to one that primes the cell for differentiation (38). Reduced pirin expression is a common feature of acute myelogenous leukemia, which results in the proliferation of immature myeloid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pirin has been proposed to be an important factor in cell differentiation (38). In progenitor cells, the activation of pirin is an important event that alters the transcription profile of the cell to one that primes the cell for differentiation (38).…”
Section: Discussionmentioning
confidence: 99%